Research on the stress concentration effects and fracture mechanisms of DC04 sheet steel with holes - Lin, Xu; Zhang, Limei; Xie, Yi (Frontiers in Materials, 2025)
DC04 sheet steel is widely used in automotive engineering because of its light weight and high ductility. The sheet steel with holes will emerge stress concentration under loading, then the peripore crack appeared around holes until the fracture occurred. The conventional analysis started around the macroscopic experiment and theoretical analysis, but the study on the evolution law and fracture mechanism of peripore cracks caused by stress concentration effect was not systematic. So, the hole stress of DC04 sheet steel with circular, oval, rectangular and diamond holes were firstly analyzed in this paper. At the same time, 15 groups of tensile tests were verified the influence of cavity shape on stress concentration. Then, taking the sheet steel with circular hole and oval hole as the research object, the evolution of aperture and stress change law were analyzed, and the corresponding empirical formula of stress concentration coefficient about net section was obtained. Finally, the microscopic crack development was observed by electron microscopy, and the crack evolution law and the fracture mechanism caused by stress concentration around the hole were analyzed. These studies will provide theoretical support for the practical engineering design.